Influence of the distance of the curing light source and composite shade on hardness of two composites - Thaís Thomé; Washington Steagall Jr; Arlene Tachibana; Sheila Regina Maia Braga; Miriam Lacalle Turbino (University of São Paulo, 2007)
This study evaluated the influence of curing tip distance, shade and filler particle size on Vickers microhardness (VHN) of composite resins. Two composites were tested: Filtek Z250 microhybrid (3M ESPE; shades A1 and A3.5) and Filtek Supreme nanofilled (3M ESPE; shades A1B and A3.5B). For each resin, 42 specimens (5 mm in diameter and 2 mm height) were prepared being 21 for each shade. The specimens were exposed using a 20-second exposure to a quartz-tungsten-halogen light source with an irradiance of approximately 560 mW/cm², at the following distances: 0 mm (surface contact), 6 mm and 12 mm from composite surface. Effectiveness of cure of different resins, shades and curing distances was determined by measuring the top and bottom hardness (VHN) of specimens using a digital microhardness tester (load: 50 g; dwell time: 45 seconds) 24 hours following curing. The hardness ratio was calculated by dividing VHN of the bottom surface by VHN of top surface. Three-way ANOVA and Tukey's post-hoc test (p<0.05) revealed statistically significant differences for all analyzed factors. As for top hardness, as microhardness ratio (bottom/top), the factors shade, distance and composite filler particle size exerted influence on resin curing. Lighter shade composites (A1 and A1B) showed higher hardness values. At 6 and 12 mm curing tip distances, hardness was lower when compared to 0 mm. The microhybrid composite resin presented higheer hardness, being its microhardness ratio satisfactory only at 0 mm for both shades and at 6 mm for the lighter shade. The nanofilled composite resin did not present satisfactory microhardness at the bottom while the microhybrid composite resin had higher hardness than the nanofilled. Composite's curing tip distance and shade can influence hardness.